2011
DOI: 10.1063/1.3573518
|View full text |Cite
|
Sign up to set email alerts
|

Vortex core scattering and pinning by impurities in nanomagnets

Abstract: The dynamical behavior of a magnetic nanoparticle contaminated by pointlike impurities is studied by using a spin dynamics numerical simulation. It was observed that the impurities can behave both as pinning (attractive) and as scattering (repulsive) sites. A Gaussian profile was observed for the interaction potential energy ranging up to two lattice parameters. Using the known values of the parameters for Permalloy-79 we have calculated the interaction energy of the vortex core with a single defect. We estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…[22]. Our results [23] indicate that the possible origins of the pinning and scattering defects in thin films can be the local reduction or increase in the exchange constant respectively, caused by a local nanoscaled structural deformation during the nanofabrication process. We believe that not all structural defects produced in the samples are pinning defects, structural scattering defects can also be produced and certainly will affect the gyrotropic frequency as pointed out in Ref.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…[22]. Our results [23] indicate that the possible origins of the pinning and scattering defects in thin films can be the local reduction or increase in the exchange constant respectively, caused by a local nanoscaled structural deformation during the nanofabrication process. We believe that not all structural defects produced in the samples are pinning defects, structural scattering defects can also be produced and certainly will affect the gyrotropic frequency as pointed out in Ref.…”
Section: Introductionmentioning
confidence: 72%
“…The authors argued that the fluctuations were due to a distribution of nanoscale defects pinning the vortex core. In a recent work [23] we showed the dynamical behavior of a magnetic nano-disk contaminated by pointlike impurities, using micromagnetic approach [24]. In this approach the nano-disk is partitioned into cubical working cells containing many atoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical works have shown that the energy and stability of these topological excitations depend on the curvature of the ferromagnetic nanoparticle [10] and their dynamical properties are affected by both: the interaction with curve defects appearing during the fabrication of the nanomagnets [11]; and the presence of magnetic/non-magnetic impurities in these magnetic nanoparticles [12].…”
Section: Introductionmentioning
confidence: 99%